2022
DOI: 10.1186/s41232-022-00196-9
|View full text |Cite
|
Sign up to set email alerts
|

Immune-instructive copolymer scaffolds using plant-derived nanoparticles to promote bone regeneration

Abstract: Background Age-driven immune signals cause a state of chronic low-grade inflammation and in consequence affect bone healing and cause challenges for clinicians when repairing critical-sized bone defects in elderly patients. Methods Poly(l-lactide-co-ɛ-caprolactone) (PLCA) scaffolds are functionalized with plant-derived nanoparticles from potato, rhamnogalacturonan-I (RG-I), to investigate their ability to modulate inflammation in vitro in neutrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…Consequently, the decreased level of NO production in macrophages/AD-MSCs cocultured on the DPS appears to be linked to a reduction in TNF-α production. It is worth noting that macrophages, in addition to cytokine and NO measurements, have a general function in phagocytosis, which is not restricted to a specific phenotype . It can be considered an influential factor besides cytokine and NO measurement in investigating M1 and M2 phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the decreased level of NO production in macrophages/AD-MSCs cocultured on the DPS appears to be linked to a reduction in TNF-α production. It is worth noting that macrophages, in addition to cytokine and NO measurements, have a general function in phagocytosis, which is not restricted to a specific phenotype . It can be considered an influential factor besides cytokine and NO measurement in investigating M1 and M2 phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that macrophages, in addition to cytokine and NO measurements, have a general function in phagocytosis, which is not restricted to a specific phenotype. 100 It can be considered an influential factor besides cytokine and NO measurement in investigating M1 and M2 phenotypes. Several studies have shown that anti-inflammatory macrophages tend to produce higher levels of IL-10 and exhibit an increased capacity for phagocytosing apoptotic thymocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Plant-derived nanoparticles from potato containing rhamnogalacturonan-I (with relatively higher amount of gallactose) have been used for poly (L-lactide-co-ɛ-caprolactone) scaffolds functionalization revealing a downregulation of pro-inflammatory gene markers and promotion of osteogenic markers [ 79 ]. The same plant-derived pectin, rhamnogalacturonan-I, has been employed for the nanocoating of im-plants influencing osteoblast proliferation, mineralization and gene expression (Runt-related transcription factor 2 (Runx2), alkaline phosphate (ALP), osteocalcin (Bglap), α-1 type I collagen (Col1a1), receptor activator of NF-κB ligand (RANKL)) [ 80 ].…”
Section: The Innovative Administration and Application Of Plant Extra...mentioning
confidence: 99%
“…Psidium guajava [103] malvidin, cyanidin and delphinidin inhibition of MSC adipogenesis and downregulation of FABP4 and adiponectin genes. Solanum tuberosum [77,78] Crocin, Crocetin ↑ ALP activity and ALP mRNA expression in MSCs Crocus sativus L. [108] Sinapic acid activation of TGF-β1/BMP/Smads/Runx2 signaling pathways => osteoblast differentiation…”
Section: Triterpenes (Ursolic Acid 2α-hydroxyursolic Acid)mentioning
confidence: 99%
“…Plant-derived nanoparticles from potato containing rhamnogalacturonan-I (with relatively higher amount of gallactose) were used for poly(L-lactide-co-ɛ-caprolactone) scaffolds functionalization revealing a downregulation of pro-inflammatory gene markers and promotion of osteogenic markers [77]. The same plant-derived pectin, rhamnogalacturonan-I, was employed for nanocoating of im-plants influencing osteoblast proliferation, mineralization, and gene expression (Runt-related transcription factor 2 (Runx2), alkaline phosphate (ALP), osteocalcin (Bglap), α-1 type I collagen (Col1a1), receptor activator of NF-κB ligand (RANKL)) [78].…”
Section: The Innovative Administration and Application Of Plant Extra...mentioning
confidence: 99%